-3,636:0,6+2,6*(5-1,1)= -3,8*(4-4,9)+13,4*(3-2,8)=

-3,636:0,6+2,6*(5-1,1)=  -3,8*(4-4,9)+13,4*(3-2,8)=
Гость
Ответ(ы) на вопрос:
Гость
-3,636:0,6+2,6*(5-1,1)=6,06+2,6*3,9=6,06+10,14=16,2 -3,8*(4-4,9)+13,4*(3-2,8)=-3,8*(-0,9)+13,4*0,2=3,42+2,68=6,1 Отметьте как лучшее, пожалуйста!!
Гость
-3,636:0,6+2,6*(5-1,1)=4.08 1)5-1.1=3.9 2)-3.636:0.6=-6.06 3)2.6*3.9=10.14 4)-6.06+10.14=4.08 -3,8*(4-4,9)+13,4*(3-2,8)=6.1 1)4-4.9=-0.9 2)3-2.8=0.2 3)-3.8*(-0.9)=3.42 4)13.4*0.2=2.68 5)3.42+2.68=6.1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы